2022
DOI: 10.1177/21582440221095009
|View full text |Cite
|
Sign up to set email alerts
|

Passion and Flow at Work for the Reduction of Exhaustion at Work in Nursing Staff

Abstract: Passion for work is an important individual factor related to the quality of working life. Flow at work is an optimal experience in which the individual is immersed in, loves and enjoys the work. The aim of the study is to investigate the relationship between passion for work (harmonious and obsessive), flow at work (as a mediator) and exhaustion in a sample of Italian nurses. About 270 nurses participated in the study: this profession is characterized by intrinsic motivation but is also subjected to fatigue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
(126 reference statements)
0
4
0
1
Order By: Relevance
“…We note that all seven factors of the PEBS-which stemmed from participants' open-text responses-have appeared in various forms in previous literature. For instance, employees who experience greater passion for their work produce higher quality in their work (Ho et al, 2011), work longer hours (Curran et al, 2015;Pollack et al, 2020), and are more immersed in their work (Zito et al, 2022). Experiencing more intense emotions and motivation is reflected in the theoretical conceptualization of passion (e.g., "a strong feeling [...] that sparks intentions and behaviors [...]"; Jachimowicz et al, 2018, p. 9980), both for positive and negative emotions (Jachimowicz et al, 2019;Wolf et al, 2016).…”
Section: Discussion Of Studies 2a 2b and 2cmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that all seven factors of the PEBS-which stemmed from participants' open-text responses-have appeared in various forms in previous literature. For instance, employees who experience greater passion for their work produce higher quality in their work (Ho et al, 2011), work longer hours (Curran et al, 2015;Pollack et al, 2020), and are more immersed in their work (Zito et al, 2022). Experiencing more intense emotions and motivation is reflected in the theoretical conceptualization of passion (e.g., "a strong feeling [...] that sparks intentions and behaviors [...]"; Jachimowicz et al, 2018, p. 9980), both for positive and negative emotions (Jachimowicz et al, 2019;Wolf et al, 2016).…”
Section: Discussion Of Studies 2a 2b and 2cmentioning
confidence: 99%
“…Employees may also express their passion through an increased quantity of their work (Curran et al, 2015;Pollack et al, 2020); for instance, one study found that participants describe passionate employees as those who "often work outside of the regular 9 a.m. to 5 p.m" (Cho & Jiang, 2022, p. 1364. Some research also suggests that passion is characterized by greater immersion into one's work, i.e., by being particularly focused and unwilling to take a break, or feeling that little time has passed (Csikszentmihalyi et al, 2014;Zito et al, 2022). Based on these and related findings, we propose that people's experience of passion may lead them to express their passion through a broader variety of behaviors than prior research has focused on-and, critically, that their levels of extraversion shape how they express their passion, and how they are subsequently perceived by others.…”
Section: Passion Can Be Expressed In a Variety Of Waysmentioning
confidence: 99%
“…An essential personal component relating to the quality of the working life is one's level of job passion. It causes a feeling of flow during work, which appears to be advantageous to nurses' psychological health and prevents tiredness (Zito et al, 2022). Organizational dehumanizing experiences could be a common issue in healthcare organizations at this time.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Given the difficulties of the pandemic and its impact on healthcare personnel, who are subjected to various additional stressful situations, it is crucial to comprehend the effects of this unusual health crisis (Danae et al, 2017; Buheji A key element that might affect individuals' wellbeing at work and, consequently, the quality of work life is their level of passion for their profession. Investing time in one's work indicates passion, which has an impact on performance (Zito et al, 2022). Persons who are passionate about something genuinely invest a lot of time and energy into it because they believe it to be very important.…”
Section: Introductionmentioning
confidence: 99%
“…En lo que hace a sus consecuencias, la evidencia empírica ha demostrado recurrentemente la vinculación entre flow y satisfacción laboral (Bakker, 2008;Fullagar & Delle Fave, 2017;Tavčar, & Arzenšek, 2019) señalando, además, que el primero emerge como un poderoso predictor de la segunda. Del mismo modo, son probadas las conexiones positivas con engagement (Dai & Wang, 2023;Fullagar & Delle Fave, 2017, Sanford Ayres Farina, dos Reis Rodrigues & Hutz, 2018Yan & Donaldson, 2020) implicación y pasión en el trabajo (Salessi & Omar, 2018b;Salessi & Omar, 2020b;Zito et al, 2022); así como con el compromiso, la identificación y la lealtad organizacional (Kim, Bonn, Lee & Kim, 2019;Wang & Shaheryar, 2020). Del mismo modo, investigaciones recientes demuestran las vinculaciones entre flow, performance, desempeño laboral y conductas extra-rol, tales como comportamientos proactivos e innovadores (Soriano et al, 2021;Stollberger & Debus, 2020).…”
Section: Flowunclassified